Cancer‐related outcomes in kidney allograft recipients in England versus New York State: a comparative population‐cohort analysis between 2003 and 2013. (30th January 2017) - Jackson‐Spence, Francesca; Gillott, Holly; Tahir, Sanna; Nath, Jay; Mytton, Jemma; Evison, Felicity; Sharif, Adnan
Abstract: It is unclear whether cancer‐related epidemiology after kidney transplantation is translatable between countries. In this population‐cohort study, we compared cancer incidence and all‐cause mortality after extracting data for every kidney‐alone transplant procedure performed in England and New York State (NYS) between 2003 and 2013. Data were analyzed for 18, 493 and 11, 602 adult recipients from England and NYS respectively, with median follow up 6.3 years and 5.5 years respectively (up to December 2014). English patients were more likely to have previous cancer at time of transplantation compared to NYS patients (5.6% vs. 3.5%, P  < 0.001). Kidney allograft recipients in England versus NYS had increased cancer incidence (12.3% vs. 5.9%, P  < 0.001) but lower all‐cause mortality during the immediate postoperative stay (0.7% vs. 1.0%, P  = 0.011), after 30‐days (0.9% vs. 1.8%, P  < 0.001) and after 1‐year post‐transplantation (3.0% vs. 5.1%, P  < 0.001). However, mortality rates among patients developing post‐transplant cancer were equivalent between the two countries. During the first year of follow up, if patients had an admission with a cancer diagnosis, they were more likely to die in both England (Odds Ratio 4.28 [95% CI: 3.09–5.93], P  < 0.001) and NYS (Odds Ratio 2.88 [95% CI: 1.70–4.89], P  < 0.001). Kidney allograft recipients in NYS demonstrated higher hazard ratios for developing kidney transplant rejection/failure compared to England on Cox regression analysis. Our analysis demonstrates significant differences in cancer‐related epidemiology between kidney allograft recipients in England versus NYS, suggesting caution in translating post‐transplant cancer epidemiology between countries. Abstract : Cancer is a common cause of morbidity, mortality and patient concern after kidney transplantation. While cancer‐related epidemiology is often translated between kidney allograft recipients from different countries, this study suggests caution and recommends more population‐specific studies are warranted.